A New Oleanane Type Saponin from the Aerial Parts of Nigella sativa with Anti-Oxidant and Anti-Diabetic Potential - Parveen, Amna; Farooq, Muhammad Asim; Kyunn, Whang Wan (Molecules (Basel, Switzerland), 2020)
Natural product studies explore potential and interesting new compounds to discover innovative drugs. Nigella sativa (N. sativa) (Ranunculaceae) is traditionally used to treat diabetes. Flavonoids and triterpenoid mostly show anti-diabetic activity. The current study aim to identify new compounds by a systematic study of the anti-oxidant and anti-diabetic activity of aerial parts of N. sativa concerning. Phytochemicals were isolated from the methanolic extract of aerial parts of the plant by column chromatography and identified by nuclear magnetic resonance spectroscopy and mass spectroscopy. A new triterpenoid saponin glycoside was isolated along with flavonoids. The anti-diabetic study was carried out by DPPH, ABTS, α -glucosidase, and protein tyrosine phosphatase 1B assays at doses of 12.5 to 250 µM. The isolated phytochemicals were identified as 3-O-(β-d-xylopyranosyl-(1-3)-α-l-rhamnopyrnaosyl-(1-2)-α-l-arabinopyranosyl]-28-O-(α-l-rhamno-pyranosyl-(1-4)-β-d-glucopyranosyl-(1-6)-β-d-glucopyranosyl] hederagenin (1), flaccidoside III (2), catechol (3), quercetin-3-gentiobiosides (4), magnoflorine (5), nigelflavonoside B (6), nigelloside (7), quercetin sphorotrioside (8), kaempferol-3, 7-diglucoside (9), kaempferol 3-O-rutinoside (10), rutin (11), 3-O-[α-l-rhamnopyranosyl-(1→2)-α-l-arabinopyranpsylhederagenin (12), 3β,23,28-trihydroxyolean-12-ene-3-O-α-l-arabinopyranoside(1→4)-a-rhamnopyranosyl,(1→4)-β-d-gluco-pyranoside (13), 3-O-α-l-rhamnopyranosyl-(1→2)-α-l-arabinopyranpsyl]-28-O-β-d-gluco-pyranosyl hederagenin (14), and α-hederin (15). These were isolated and are reported for the first time in this study. Compared 13 was identified as a new compound. Compound 2 was isolated for first time from the genus Nigella. Compound 6 was found to be the most active in the DPPH, and ABTS assays and compound 10 was found to be the most active in the α-glucosidase assay, with IC50 32.7 ± 0.1, 95.18 ± 0.9, 214.5 ± 0.0 µΜ, respectively. Compound 12, at a dose of 125 µΜ, showed anti-diabetic activity in a PTP1B assay with IC50 91.30 ± 2.5 µΜ. In conclusion, the anti-diabetic activity of N. sativa is due to its flavonoids and TTSGs. Therefore, our studies suggest that the aerial parts of N. sativa are also a valuable and alternate source of valuable phytochemicals that could be used to develop anti-oxidant and anti-diabetic medicines.